Ketamine Infusion for Adjunct Sedation in Mechanically Ventilated Adults. Issue 2 (10th January 2018) - Groetzinger, Lara M.; Rivosecchi, Ryan M.; Bain, William; Bahr, Marshall; Chin, Katherine; McVerry, Bryan J.; Barbash, Ian
Abstract : Background: Many critically ill patients receive ketamine for adjunct sedation despite a paucity of evidence on its use, dosing, and monitoring in this setting. Objective: To describe the dosing and safety considerations of ketamine for adjunct sedation in a population of mechanically ventilated critically ill patients targeting light sedation. Methods: We conducted a retrospective review of mechanically ventilated patients receiving continuous ketamine infusion between January 2012 and April 2016. Data included dosing, effect of ketamine on other sedatives, total sedative use, Riker Sedation‐Agitation Scale (SAS) scores, adverse drug reactions (ADRs), and hemodynamic variables. Results: Ninety‐one patients were included in the analysis. Ketamine was infused at a median dosage of 0.41 mg/kg/hour (range 0.04–2.5 mg/kg/hr) for up to 14.7 days (median 2.8 days). Concomitant sedatives were reduced or discontinued, without the initiation of an additional sedative, in 57 patients (63%) within 24 hours of initiating ketamine. Propofol was most commonly discontinued (16 patients, 36%), followed by benzodiazepines (12 patients, 27%). There was an increase in the number of SAS scores documented in goal in the 24‐hour period after ketamine initiation compared with the immediate 24 hours before (61% vs 55%, p=0.001). Patients were less frequently agitated, defined as SAS >4, after the initiation of ketamine (27% vs 33%, p=0.005). Seven patients (7.7%) required discontinuation of ketamine infusion for an ADR. There were no significant changes in hemodynamic variables after the initiation of ketamine. Conclusions: Continuous ketamine infusion for adjunct light sedation was well tolerated in a cohort of critically ill adults, with an acceptable safety profile. Prospective studies of ketamine infusion are warranted to further establish its efficacy as a sedative in this population.